From Liberal Globalisation to Economic Nationalism? - Lane, D. (Социология: теория, методы, маркетинг, 2019)
Contemporary counter movements, universally dubbed as "populist" differ in many respects, but they all agree on a number of significant political and economic issues. First, a condemnation of the economic polices shared until now by the major electoral parties. Second, a criticism that the economic mechanism and political process have led to social polarisation. Third, a contention that electoral democracy has delivered an oligarchic bloc of irresponsible elites who have utilised neo-liberalism to legitimate their own interests.